EDUKASI GIZI SEIMBANG DAN PEMERIKSAAN PENUNJANG PADA REMAJA - Tezi Kharina Aprezia; Maria Nuraeni; Titin Dewi Sartika Silaban; Margareta Melani; Lezi Mayang Sari (INTEGRITAS : Jurnal Pengabdian, 2025)
Adolescence is an important period in the life cycle characterized by rapid physical, psychological, and social changes. During this phase, energy and nutrient requirements increase significantly to support organ development and metabolic function. Nutritional problems among adolescents in Indonesia remain a serious challenge. The 2018 Riskesdas reported that the prevalence of anemia in adolescents aged 15–24 years reached 32%, and in adolescent girls the figure was even higher due to blood loss during menstruation and low iron intake. Data shows an increase in the prevalence of overnutrition in adolescents, which is a risk factor for non-communicable diseases (NCDs) such as diabetes, hypertension, and dyslipidemia in adulthood. This PKM activity aims to educate female adolescents who are prospective babysitters on the importance of maintaining a balanced diet and understanding the results of health examinations for these female adolescents. The PKM method involves counseling adolescents using audiovisual materials and supporting examinations. The results of this PKM show that most of the participants were 18-21 years old, totaling 12 people. This PKM activity also received positive feedback, with prospective babysitters expressing enthusiasm for the PKM activities through question nd answer discussions. The questionnaire evaluation results also showed that the participants gained an understanding of the importance of maintaining a balanced diet for the body. This PKM activity is expected to serve as a source of information for teenagers and readers on the importance of maintaining a balanced diet to prevent health problems from an early age.